Adoption, implementation and sustainability of school-based physical activity and sedentary behaviour interventions in real-world settings: a systematic review - Samuel Cassar; Jo Salmon; Anna Timperio; Patti-Jean Naylor; Femke van Nassau; Ana María Contardo Ayala; Harriet Koorts (BMC, 2019)
Abstract Background Globally, many children fail to meet the World Health Organization's physical activity and sedentary behaviour guidelines. Schools are an ideal setting to intervene, yet despite many interventions in this setting, success when delivered under real-world conditions or at scale is limited. This systematic review aims to i) identify which implementation models are used in school-based physical activity effectiveness, dissemination, and/or implementation trials, and ii) identify factors associated with the adoption, implementation and sustainability of school-based physical activity interventions in real-world settings. Methods The review followed PRISMA guidelines and included a systematic search of seven databases from January 1st, 2000 to July 31st, 2018: MEDLINE, EMBASE, CINAHL, SPORTDiscus, PsycINFO, CENTRAL, and ERIC. A forward citation search of included studies using Google Scholar was performed on the 21st of January 2019 including articles published until the end of 2018. Study inclusion criteria: (i) a primary outcome to increase physical activity and/or decrease sedentary behaviour among school-aged children and/or adolescents; (ii) intervention delivery within school settings, (iii) use of implementation models to plan or interpret study results; and (iv) interventions delivered under real-world conditions. Exclusion criteria: (i) efficacy trials; (ii) studies applying or testing school-based physical activity policies, and; (iii) studies targeting special schools or pre-school and/or kindergarten aged children. Results 27 papers comprising 17 unique interventions were included. Fourteen implementation models (e.g., RE-AIM, Rogers' Diffusion of Innovations, Precede Proceed model), were applied across 27 papers. Implementation models were mostly used to interpret results (n = 9), for planning evaluation and interpreting results (n = 8), for planning evaluation (n = 6), for intervention design (n = 4), or for a combination of designing the intervention and interpreting results (n = 3). We identified 269 factors related to barriers (n = 93) and facilitators (n = 176) for the adoption (n = 7 studies), implementation (n = 14 studies) and sustainability (n = 7 studies) of interventions. Conclusions Implementation model use was predominately centered on the interpretation of results and analyses, with few examples of use across all study phases as a planning tool and to understand results. This lack of implementation models applied may explain the limited success of interventions when delivered under real-world conditions or at scale. Trial registration PROSPERO (CRD42018099836).